The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1002/eat.22479
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary evaluation of the validity of binge‐eating disorder defining features in a community‐based sample

Abstract: Objective-Little empirical attention has been paid to the DSM-5 definition of Binge Eating Disorder (BED), particularly to the associated features of binge episodes. The present study sought to determine how the associated features and undue influence of weight/shape on self-evaluation contribute to evidence of a clinically significant eating disorder.Method-Secondary analyses were conducted on data (N = 80; 76.3% women, 76.3% Caucasian, ages 18-43) collected through an epidemiological study of eating patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 25 publications
0
14
1
Order By: Relevance
“…Therefore, individuals evaluated for BED are required to characterize “typical” binge‐eating episodes over the past three months, which may produce recall errors. Retrospective research suggests that the presence of DSM indicators predicts BED diagnostic status (White & Grilo, ), while other data suggest that the indicators have poor internal consistency and do not reliably predict eating‐related distress in community samples (Klein, Forney, & Keel, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, individuals evaluated for BED are required to characterize “typical” binge‐eating episodes over the past three months, which may produce recall errors. Retrospective research suggests that the presence of DSM indicators predicts BED diagnostic status (White & Grilo, ), while other data suggest that the indicators have poor internal consistency and do not reliably predict eating‐related distress in community samples (Klein, Forney, & Keel, ).…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective research suggests that the presence of DSM indicators predicts BED diagnostic status (White & Grilo, 2011), while other data suggest that the indicators have poor internal consistency and do not reliably predict eating-related distress in community samples (Klein, Forney, & Keel, 2016).…”
mentioning
confidence: 99%
“…On the other hand, overvaluation has also been recently found not to predict distress related to binge eating in a community sample (Klein, Forney, & Keel, 2016). Concerning the role of obesity, adults with BED in the general population are around three times more likely than people without eating disorders to be mild to moderately obese and 6.5 times more likely to be severely obese (Kessler et al, 2013).…”
mentioning
confidence: 95%
“…The authors also tested both positive and negative predictive power to identify a Criterion B symptom threshold that maximized identification of binge-eating cases and minimized false positives, with results supporting the current threesymptom threshold for identifying binge eating in a BED/BN sample. Klein et al (2016) assessed how each Criterion B symptom was associated with distress in a majority-BED sample. Logistic regression revealed that "feeling disgusted/depressed/guilty" (B5) was the only Criterion B symptom that uniquely predicted distress about binge eating or associated weight gain.…”
Section: Criterion B Symptom Validitymentioning
confidence: 99%